On the Adsorption of Chiral Propylene Oxide onto Pd(111): A DFT Study - A. Gil-Rebaza; D. Linares; G. Zgrablich (Adsorption Science & Technology)
The adsorption of chiral propylene oxide onto a Pd(111) single crystal was studied via ab initio calculations based on plane-wave Density Functional Theory. Different adsorption sites and different molecular configurations, both tilted and flat, have been analyzed. The on-top site is the preferred one for all configurations. The adsorption energy varies over a wide range of values spanning the range from ca. 10–20 kcal/mol for both the inclination of the molecule with respect to the surface and the coverage.